The Cholinergic Drug Galantamine Alleviates Oxidative Stress Alongside Anti-inflammatory and Cardio-Metabolic Effects in Subjects With the Metabolic Syndrome in a Randomized Trial - Sangaleti, Carine Teles; Katayama, Keyla Yukari; De Angelis, Kátia; Lemos de Moraes, Tércio; Araújo, Amanda Aparecida; Lopes, Heno F.; Camacho, Cleber; Bortolotto, Luiz Aparecido; Michelini, Lisete Compagno; Irigoyen, Maria Cláudia; Olofsson, Peder S.; Barnaby, Douglas P.; et al. (Frontiers in Immunology, 2021)
Background: The metabolic syndrome (MetS) is an obesity-associated disorder of pandemic proportions and limited treatment options. Oxidative stress, low-grade inflammation and altered neural autonomic regulation, are important components and drivers of pathogenesis. Galantamine, an acetylcholinesterase inhibitor and a cholinergic drug that is clinically-approved (for Alzheimer’s disease) has been implicated in neural cholinergic regulation of inflammation in several conditions characterized with immune and metabolic derangements. Here we examined the effects of galantamine on oxidative stress in parallel with inflammatory and cardio-metabolic parameters in subjects with MetS. Trial design and methods: The effects of galantamine treatment, 8 mg daily for 4 weeks or placebo, followed by 16 mg daily for 8 weeks or placebo were studied in randomly assigned subjects with MetS (n=22 per group) of both genders. Oxidative stress, including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase activities, lipid and protein peroxidation, and nitrite levels were analyzed before and at the end of the treatment. In addition, plasma cytokine and adipokine levels, insulin resistance (HOMA-IR) and other relevant cardio-metabolic indices were analyzed. Autonomic regulation was also examined by heart rate variability (HRV) before treatment, and at every 4 weeks of treatment. Results: Galantamine treatment significantly increased antioxidant enzyme activities, including SOD (+1.65 USOD/mg protein, [95% CI 0.39 to 2.92], P=0.004) and CAT (+0.93 nmol/mg, [95% CI 0.34 to 1.51], P=0.01), decreased lipid peroxidation (thiobarbituric acid reactive substances, (log scale 0.72 pmol/mg, [95% CI 0.46 to 1.07], P=0.05) and systemic nitrite levels (log scale 0.83 umol/mg protein, [95% CI 0.57 to 1.20], P=0.04) compared with placebo. In addition, galantamine significantly alleviated the inflammatory state and insulin resistance, and decreased the low frequency/high frequency ratio of HRV, following 8 and 12 weeks of drug treatment. Conclusion: Low-dose galantamine alleviates oxidative stress, alongside beneficial anti-inflammatory, and metabolic effects, and modulates neural autonomic regulation in subjects with MetS. These findings are of considerable interest for further studies with the cholinergic drug galantamine to ameliorate MetS.